2012
DOI: 10.1590/s0100-72032012000900002
|View full text |Cite
|
Sign up to set email alerts
|

Sífilis em parturientes: aspectos relacionados ao parceiro sexual

Abstract: PURPOSES:To analyze the sociodemographic and behavioral profile of sex partners, the proportion of those inadequately treated as well as to verify how many of them were inadequately treated and why some were not treated. METHODS: Quantitative study with data collected from May to October, 2008 at five public maternities in Fortaleza, Ceará. A survey was carried out with parturients who were hospitalized with syphilis and had a stable sex partner. We analyzed sociodemographic variables and those related to comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
41

Year Published

2016
2016
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 17 publications
0
20
0
41
Order By: Relevance
“…Inadequate treatment is extremely common, as seen in this work and several previous studies 11,15,16,18 , and its main cause is related to the treatment of partners of pregnant women. A study by Campos et al 33 investigated the reason for not treating partners and found that they were informed about the disease and but they simply did not follow the treatment, because of a cultural issue regarding men being sick. In this work, only one partner was oriented as described in the medical record, but no pregnant woman was considered adequately treated.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate treatment is extremely common, as seen in this work and several previous studies 11,15,16,18 , and its main cause is related to the treatment of partners of pregnant women. A study by Campos et al 33 investigated the reason for not treating partners and found that they were informed about the disease and but they simply did not follow the treatment, because of a cultural issue regarding men being sick. In this work, only one partner was oriented as described in the medical record, but no pregnant woman was considered adequately treated.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of vulnerability, investigators consider some populations as more likely to acquire syphilis: individuals living in seclusion, homeless people, drug users, men who have sex with men (MSM), those co-infected with human immunodeficiency virus (HIV), and pregnant women [8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…From the professional practice criteria, in addition to the failures in treatment of partners, there was low compliance in the cure control of pregnant women with less opportunity to identify failures in the treatment of pregnant women. Inadequate control of the treatment of pregnant women has also been reported by Silva and Campos in studies in the state of Ceará/Brazil.…”
Section: Discussionmentioning
confidence: 54%